The nature of counterion and photovoltaic properties of cationic polymethine dyes - Bulavko, G.V.; Ishchenko, A.A. (Reports of the National Academy of Sciences of Ukraine, 2015)
The anion nature of cationic polymethine dyes in polymer composites has been found to affect the photovoltage value. According to the investigations of spectral-luminescent properties, polymethines form contact ion pairs. The difference in the behavior of anions is determined by their ability of the photoinduced electron transfer in these pairs.